Bank Indonesia Policy in the National Banking Crisis Resolution - Surti Yustianti; Mohammad Roesli (Faculty of Law, Merdeka University Surabaya, 2018)
This study analyzes the philosophy of banking policies which have implications for the criminal offense. In this regard, Bank Indonesia's decision is in conformity with the authority and office attached to Bank Indonesia officials. Policies made by Bank Indonesia is right or not, is bound by the principle of wise and good etiquette. Bank Indonesia officials have the authority associated with the position. If there are elements that are not good etiquette and undiplomatic in authority that caused state losses then policies can be categorized as a criminal offense banking. The aim of this study was to analyze and find Philosophy as Bank Indonesia Policy In the Bank Restructuring. Type of research is a normative legal research. This study uses the legislative approach, conceptually. Banking policy which resulted in a criminal act can be seen from the administrative aspect, and a criminal in a lawsuit conducted by Bank Indonesia officials. If Bank Indonesia officials make mistakes in order to carry out regulatory policies, the criminal incurred should be charged to the official.